2010
DOI: 10.1038/ng.594
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in TMEM216 perturb ciliogenesis and cause Joubert, Meckel and related syndromes

Abstract: Joubert syndrome (JBTS), related disorders (JSRD) and Meckel syndrome (MKS) are ciliopathies. We now report that MKS2 and JBTS2 loci are allelic and due to mutations in TMEM216, encoding an uncharacterized tetraspan transmembrane protein. JBTS2 patients displayed frequent nephronophthisis and polydactytly, and two cases conformed to the Oro-Facio-Digital type VI phenotype, whereas skeletal dysplasia was common in MKS fetuses. A single p.R73L mutation was identified in all patients of Ashkenazi Jewish descent (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
242
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 259 publications
(253 citation statements)
references
References 35 publications
10
242
0
1
Order By: Relevance
“…Despite two patients displaying an occipital encephalocele, no ARL13B variants have been found in Meckel syndrome fetuses (Cantagrel et al 9 and personal data), although Meckel syndrome has been shown to be the extreme lethal phenotype of JS for other genes. [29][30][31][32][33] In conclusion, we have identified a novel homozygous missense variant in ARL13B/JBTS8 in a JS patient with retinal involvement and obesity. We have shown that this variant is hypomorphic, as it is unable to rescue efficiently either the arl13b sco zebrafish phenotype or the deficiencies in Arl13b hnn MEFs.…”
Section: Discussionmentioning
confidence: 68%
“…Despite two patients displaying an occipital encephalocele, no ARL13B variants have been found in Meckel syndrome fetuses (Cantagrel et al 9 and personal data), although Meckel syndrome has been shown to be the extreme lethal phenotype of JS for other genes. [29][30][31][32][33] In conclusion, we have identified a novel homozygous missense variant in ARL13B/JBTS8 in a JS patient with retinal involvement and obesity. We have shown that this variant is hypomorphic, as it is unable to rescue efficiently either the arl13b sco zebrafish phenotype or the deficiencies in Arl13b hnn MEFs.…”
Section: Discussionmentioning
confidence: 68%
“…The INPP5E phenotypic spectrum appears to largely overlap with that related to AHI1 mutations; 18 conversely, none of the INPP5E-mutated patients presented polydactyly or encephalocele, two features that are often associated with mutations in genes also causative of MKS, such as TMEM216, CEP290, TMEM67 or RPGRIP1L. 5,[19][20][21] In one patient with pure JS (COR28), only a single heterozygous INPP5E mutation could be detected, despite complete sequencing of the coding regions and canonical splice sites, and search for genomic rearrangements. Although we cannot exclude the possibility that a second pathogenic mutation resides within intronic or regulatory regions of the gene, it is also plausible that the identified change could act as a genetic modifier of the clinical phenotype in an oligogenic context, and that digenic mutations may reside in another gene.…”
Section: Discussionmentioning
confidence: 99%
“…Further weakening the causal connection between ciliary function and LR asymmetry are studies in the mouse model (where the cilia link is expected to be the strongest) on genes such as Inturned, which regulate cilia formation but do not randomize asymmetry when disrupted (Zeng et al, 2010). Mutations in TMEM216 also result in ciliopathies but no LR defects in both mice and zebrafish (Valente et al, 2010). While it has been suggested that the dissociation of ciliary mutants and LR phenotypes could be due to a maternal protein that can somehow rescue early defects (Serluca et al, 2009), together these examples demonstrate that ciliary defects can indeed be separated from LR patterning errors, and cast considerable doubt on the idea that ciliary motion is a required component of vertebrate asymmetry; these examples also confirm that LR phenotypes observed in genetic mutations of ''ciliary'' genes do not establish a causal link.…”
Section: Mutants That Do Not Show Expected Concordance Between Ciliarmentioning
confidence: 99%